Polypyrrole doping-regulated construction of dexamethasone/hydroxyapatite composite coating on titanium surface for sustained osteoinduction. (April 2021) - Wu, Huajun; Gao, Ya; Xiao, Lu; Wei, Qin; Zhang, Naiyin; Su, Zhi; Ma, Chuang; Ye, Tingjun; Wang, Yingbo
Abstract: Nano-hydroxyapatite (HA-NPs) coating on the surface of titanium is an effective way to improve the osteoinductivity of implants. However, particle agglomeration and uncontrollable structure of HA-NPs results in limited osteogenic capability. In this study, pulse electrochemical deposition method was used to drive PPy in situ, and HA-NPs as well as the osteoinductive drug Dex were introduced to PPy based on its doping characteristics to endow the titanium-based composite coating with long-term osteoinductivity during the osseointegration process. During the oxidative polymerization of PPy, PO4 3− and Dex − were doped into the main chain of PPy, and HA was formed due to the electrostatic interaction of PO4 3− and Ca 2+, finally realizing the co-deposition of HA-NPs and Dex. Dex drug release experiments showed that the doping effect of PPy has reduced the release rate of Ca 2+ from the coating and increased the physiological stability of the coating. The in vitro evaluation of osteoblasts and vascular endothelial cells showed that the number of cells increased steadily with good proliferation conditions, showing promising osteogenic ability and angiogenic property. In summary, a bioactive PPy@HA/Dex nanocomposite coating with sustained osteoinductivity was successfully constructed on the titanium surface using pulse electrochemical method. Graphical abstract: Pulse electrochemical deposition method was used to drive PPy in situ, and HA-NPs as well as the osteoinductive drug Dex were introduced to PPy based on its doping characteristics to endow the titanium-based composite coating with long-term osteoinductivity during the osseointegration process. Unlabelled Image Highlights: Long-term osteoinductivity during the osseointegration process. Regulator of hydroxyapatite and metal nanoparticles dispersion using Polypyrrole. Construct the distributed nanocomposite coatings. Good biological activity and angiogenic abilities.